2017
DOI: 10.1016/j.apcatb.2016.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Tail gas catalyzed N2O decomposition over Fe-beta zeolite. On the promoting role of framework connected AlO6 sites in the vicinity of Fe by controlled dealumination during exchange

Abstract: Tail Gas Catalyzed N2O decomposition over Fe-beta zeolite.On the promoting role of framework connected AlO6 sites in the vicinity of Fe by controlled dealumination during exchange, Applied Catalysis B, Environmental http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…The slightly lower Fe loading than the theoretical value 0.50 wt.% can be explained by the H + /Fe 3+ competition during the exchange; as discussed elsewhere. 30 The Si/Al ratio is comparable to that of the as-received zeolite material (8.9). Temperatureprogrammed reduction (TPR) characterization shed some light on the type of Fe species formed during exchange, on both the optimal and reference catalysts.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The slightly lower Fe loading than the theoretical value 0.50 wt.% can be explained by the H + /Fe 3+ competition during the exchange; as discussed elsewhere. 30 The Si/Al ratio is comparable to that of the as-received zeolite material (8.9). Temperatureprogrammed reduction (TPR) characterization shed some light on the type of Fe species formed during exchange, on both the optimal and reference catalysts.…”
Section: Resultsmentioning
confidence: 71%
“…This region Accepted 26/Dec/17 -10.1021/acs.iecr.7b04584 Final version can be accessed through the ACS website corresponds to the reduction of the Fe 3+ in exchanged positions (cations and oxocations) on the zeolite framework. 16 The optimal catalyst shows a fraction of Fe 2 O 3 species, represented by the broad peak centred at 800 K, 30 that accounts for ca. 10% of the Fe, based on a TPR quantification method for Fe-zeolites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acidity features were evaluated by pyridine-adsorbed FTIR spectroscopy ( is higher for the non-Fenton H2O2 material than the fresh counterpart; 10 % higher for the Brønsted and 50% higher for the Lewis sites. This could be explained by 1) the removal of amorphous domains (invisible to XRD) during the treatment, rendering a material with a higher intrinsic acidity and 2) due to the Al-dislodgement forming framework connected hexacoordinated Al [47]. In the case of the Fenton treatment (AP27-Fe70), similar acidity value as for the fresh ZSM-5 was found.…”
Section: Properties Of the Reactivated Materialsmentioning
confidence: 59%
“…Nitrous oxide has increased approximately linearly by about 0.8 ppb per year over the past few decades [7]. Permanent increase in N 2 O concentration in the atmosphere resulted in a search for an effective catalytic method of its decomposition [8][9][10][11][12][13][14][15][16][17][18]. The U.S. Environmental Protection Agency reported that in the years 1990-2014, almost 80% of N 2 O emitted in the US.…”
Section: Nitrous Oxide As a Greenhouse Gas And An Oxidantmentioning
confidence: 99%